A Class of Reactive Acyl-CoA Species Reveals the Non-Enzymatic Origins of Protein Acylation - Wagner, Gregory R. (Cell Metab, 2017)
The mechanisms underlying the formation of acyl protein modifications remain poorly understood. By investigating the reactivity of endogenous acyl-CoA metabolites, we found a class of acyl-CoAs that undergoes intramolecular catalysis to form reactive intermediates which non-enzymatically modify proteins. Based on this mechanism, we predicted, validated, and characterized a protein modification: 3-hydroxy-3-methylglutaryl(HMG)-lysine. In a model of altered HMG-CoA metabolism, we found evidence of two additional protein modifications: 3-methylglutaconyl(MGc)-lysine and 3-methylglutaryl(MG)-lysine. Using quantitative proteomics, we compared the ‘acylomes’ of two reactive acyl-CoA species, namely HMG-CoA and glutaryl-CoA, which are generated in different pathways. We found proteins that are uniquely modified by each reactive metabolite, as well as common proteins and pathways. We identified the tricarboxylic acid cycle as a pathway commonly regulated by acylation, and validated malate dehydrogenase as a key target. These data uncover a fundamental relationship between reactive acyl-CoA species and proteins, and define a new regulatory paradigm in metabolism.